PENGARUH LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM SEKTOR KERAJINAN TANGAN DI KABUPATEN GORONTALO - Khoirunnisa Naini; Tri Handayani Amaliah; Herlina Rasjid (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to examine the extent to which financial literacy influences the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the craft sector in Gorontalo Regency. Methods: The approach used is a quantitative approach, involving 80 respondents selected using a sampling technique based on the Slovin formula. Data collection was carried out by distributing questionnaires analyzed using a Likert scale. The entire data processing and analysis process was carried out with the help of Microsoft Excel, including instrument testing, classical assumption testing, and hypothesis testing. Results: The results of this study are expected to provide a comprehensive understanding of the impact of financial literacy on the financial performance of MSMEs in the craft sector. The research findings show that financial literacy has a significant effect on improving the financial performance of MSMEs in the region. Keywords: Financial Literacy, Financial Performance, MSMEs, Handicrafts